2018
DOI: 10.1016/j.jiph.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude towards the Middle East respiratory syndrome coronavirus among healthcare personnel in the southern region of Saudi Arabia

Abstract: There is limited microbiological and virological knowledge of MERS-CoV infection among healthcare personnel in the southern region of Saudi Arabia, although the clinical aspects are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 8 publications
(8 reference statements)
3
30
1
1
Order By: Relevance
“…For instance, 93% of social media users have good knowledge compared to those not using social media (74%) as source knowledge for the disease. Similar ndings were reported from previous studies in Vietnam (19), but different from studies in Saudi Arabia (36%) and UAE (40%) in which relatively a small percentage of HCWs used social media as a source of information about COVID-19 (18,20,21).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, 93% of social media users have good knowledge compared to those not using social media (74%) as source knowledge for the disease. Similar ndings were reported from previous studies in Vietnam (19), but different from studies in Saudi Arabia (36%) and UAE (40%) in which relatively a small percentage of HCWs used social media as a source of information about COVID-19 (18,20,21).…”
Section: Discussionsupporting
confidence: 85%
“…This result is in line with studies conducted in China, Vietnam, and Iran in which the main source of knowledge was social media (14,17,19). On the other hand, a study from Saudi and UAE showed only a small percentage of HCWs used social media as a source of knowledge about COVID-19 (18,20). This might be due to the use of global crises of outbreak social media platforms as a facilitator and distributor of COVID-19 related information for HCWs during this critical time.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, no validated tool for the assessment of the knowledge and practices of HCWs was available. We have adapted and modified tools used for the assessment of knowledge, attitude, and practice toward MERS-COV [9][10][11][12] in addition some items were formulated from WHO and CDC guidelines. Secondly, due to the lockdown, we did not design the sample to statistically represent the Lebanese population of physicians and make rigid extrapolations, but to offer for the first time, useful insights of the knowledge and practices towards COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A structured questionnaire was initially developed and designed by the authors in the English language to cover important aspects of knowledge and practice towards COVID-19 among physicians (Additional file 1). Core dimensions and items content of these two domains were identified through a review of the published literature on Middle East respiratory syndrome coronavirus (MERS-COV) [9][10][11][12] in addition to the most recent available information on COVID-19 from the World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC) websites up to 25th March 2020. Content validity of the resulting version was assessed by a panel of three experts with expertise in implementing infection control procedures and emergency preparedness.…”
Section: Instrumentationmentioning
confidence: 99%
“…resembling crown-like spikes on its surface and the main host receptor for humans seems to be the angiotensin-converting enzyme 2 (ACE2). 4 This recent COVID-19 turned into a global public health outbreak. 5,6 It is transmitted after contact with infected surfaces and with infected patient's fluids, including saliva and aerosol.…”
Section: Introductionmentioning
confidence: 99%